2004
DOI: 10.1111/j.1469-0691.2004.00956.x
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective comparison of convalescent plasma with continuing high-dose methylprednisolone treatment in SARS patients

Abstract: Treatment of severe acute respiratory syndrome (SARS) is experimental, and the effectiveness of ribavirin-steroid therapy is unclear. Forty SARS patients with progressive disease after ribavirin treatment and 1.5 g of pulsed methylprednisolone were given either convalescent plasma (n = 19) or further pulsed methylprednisolone (n = 21) in a retrospective non-randomised study. Good clinical outcome was defined as discharge by day 22 following the onset of symptoms. Convalescent plasma was obtained from recovered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
384
1
11

Year Published

2004
2004
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 371 publications
(401 citation statements)
references
References 7 publications
5
384
1
11
Order By: Relevance
“…Convalescent plasma, donated by patients who had recovered from SARS, contains neutralizing antibodies and may be useful clinically for treating other SARS patients [126,127]. Research work in the preparation of SARS-CoV-specific hyperIg from convalescent plasma donated by patients who have recovered from SARS is currently in progress.…”
Section: Convalescent Plasmamentioning
confidence: 96%
“…Convalescent plasma, donated by patients who had recovered from SARS, contains neutralizing antibodies and may be useful clinically for treating other SARS patients [126,127]. Research work in the preparation of SARS-CoV-specific hyperIg from convalescent plasma donated by patients who have recovered from SARS is currently in progress.…”
Section: Convalescent Plasmamentioning
confidence: 96%
“…Although randomized placebo-controlled trials evaluating passive postexposure prophylaxis in at-risk groups have not been undertaken, a retrospective analysis of outcomes in a limited human study using plasma from convalescent SARS patients suggested that passive immunization may shorten hospitalization without obvious adverse effects in patients (171). Passive immunization has been examined in animal models.…”
Section: Passive Immunizationmentioning
confidence: 98%
“…The practice of administering polyclonal immunoglobulins isolated from hyperimmune sera of animal or human origin, introduced by Von Behring and Kitasato, has been used extensively in prophylactic as well as in therapeutic settings [158]. Passive transfer of polyclonal immunoglobulins from convalescent SARS patients was used during the SARS epidemic as a therapeutic measure and a positive effect of the therapy is reported [159,160]. However, the risks related to the use of human blood products make them problematic as a standard therapy.…”
Section: Vaccines Passive Immunizationmentioning
confidence: 98%